Study on suspended sediment and ammonia distribution pattern in Tioman Island - Yusof, Muhammad Hamizan; Saad, Shahbudin; Mohammad Noor, Normawaty (2013)
A study on suspended sediment and ammonia distribution pattern was conducted in Tioman Island, Pahang for 3 months started from August to October 2012. This study aims to determine the sedimentation rates and ammonia concentrations in Tioman. The study area was divided into 14 stations that represent the whole Island. Samples of suspended sediment were collected using sediment trap deployed at 4 locations namely Genting, Renggis, Teduh and Benuang. Water samples for ammonia analysis were collected using the siphon technique at all sampling stations. The result of this study showed that sedimentation rates and ammonia concentration level were higher in the developed area compared to the undeveloped area. The sedimentation rate was higher at Genting (1.908 mg.cm-2.day-1) followed by Renggis Island (1.737 mg.cm-2.day-1). Whereas in Teduh and Benuang the sedimentation rates were slightly lower with 1.395 mg.cm-2.day-1 and 1.453 mg.cm-2.day-1 respectively. Ammonia concentration showed the highest at Juara (2.74 ± 0.29 µM/L) followed by Renggis Island (2.00 ± 0.95 µM/L). Statistical analysis was proved that there was a significant difference between sedimentation rates and sites. The highest nutrient level of ammonia was 2.74µM/L but, the concentration levels were still in the permissible limit. Nevertheless, continuous monitoring should be carried out in order to ensure the nutrient levels are still at the safe level.